Silicon Isotopic Composition of Dry and Wet-Based Glaciers in Antarctica - Hatton, Jade E.; Hendry, Katharine R.; Hirst, Catherine; Opfergelt, Sophie; Henkel, Susann; Silva-Busso, Adrián; Welch, Susan A.; Wadham, Jemma L.; Lyons, W. Berry; Bagshaw, Elizabeth; Staubwasser, Michael; McKnight, Diane M. (Frontiers in Earth Science, 2020)
Glaciers and ice sheets export significant amounts of silicon (Si) to downstream ecosystems, impacting local and potentially global biogeochemical cycles. Recent studies have shown Si in Arctic glacial meltwaters to have an isotopically distinct signature when compared to non-glacial rivers. This is likely linked to subglacial weathering processes and mechanochemical reactions. However, there are currently no silicon isotope (δ30Si) data available from meltwater streams in Antarctica, limiting the current inferences on global glacial silicon isotopic composition and its drivers. To address this gap, we present dissolved silicon (DSi), δ30SiDSi and major ion data from meltwater streams draining a polythermal glacier in the region of the West Antarctic peninsula (King George Island) and a cold-based glacier in East Antarctica (Commonwealth Stream, McMurdo Dry Valleys). These data, alongside other global datasets, improve our understanding of how contrasting glacier thermal regime can impact upon Si cycling and therefore the δ30SiDSi composition. We find a similar δ30SiDSi composition between the two sites, with the streams on King George Island varying between -0.23 and +1.23‰ and the Commonwealth stream varying from -0.40 to +1.14‰. However, meltwater streams in King George Island have higher DSi concentrations, and the two glacial systems exhibit opposite DSi - δ30SiDSi trends. These contrasts likely result from differences in weathering processes, specifically the role of subglacial processes (King George Island) and, supraglacial processes followed by in-stream weathering in hyporheic zones (Commonwealth Stream). These findings are important when considering likely changes in nutrient fluxes from Antarctic glaciers under climatic warming scenarios and consequent shifts in glacial thermal regimes.